Pengaruh Kompetensi dan Beban Kerja Terhadap Motivasi Kerja yang Berimplikasi Terhadap Kinerja Pegawai pada Badan Penelitian dan Pengembangan Daerah Kabupaten Tanjung Jabung Timur - Putra, Candra Dwi; Suryani, Arna; Sudirman, Sudirman (Universitas Batanghari Jambi, 2024)
This research aims to understand the correlation between three main factors, namely workload, skill level, and worker motivation in carrying out their duties at the Regional Research and Development Agency of East Tanjung Jabung Regency. The focus of this research is to evaluate the impact of competency and workload on work motivation through analysis of employee performance in the institution. The research method used was a combination of quantitative and descriptive verification approaches, using path analysis techniques and involving 65 respondents as samples. The results of the research show that the competency and motivation of employees in the Balitbangda of East Tanjung Jabung Regency have a very high level, while the workload is considered very appropriate, and employee performance is considered high. These findings support the research premise. The analysis states that the combination of skills and workload has a significant influence on employee motivation. Motivation is also slightly influenced by competence and workload. Employee performance is identified as a variable that is significantly influenced by competency and workload. In addition, it was found that there was a partial and statistically significant relationship between competency and workload and employee performance. Motivation was also proven to have a significant influence on employee performance. Overall, the analysis shows that the performance of employees at Balitbangda East Tanjung Jabung Regency is influenced by a combination of competency, workload and motivation. The direct influence reached 35.6%, while the indirect and total influence were 11.8% and 47.4% respectively.